Helminths and intestinal microbiota interaction: role in the development of noncommunicable diseases - T. S. Sokolova; O. S. Fedorova; I. V. Saltykova; V. A. Petrov; M. M. Fedotova; Yu. V. Kovshirina; I. A. Deev; L. M. Ogorodova (Бюллетень сибирской медицины)
There is an increase in the prevalence of chronic, noncommunicable diseases, including allergic and autoimmune diseases in developed countries. In this regard, the study of factors modifying the population’s immune response is very important.According to the “old friends” hypothesis , insufficiency of infectious stimulation and decrease in prevalence of helminthiasis are associated with development of noncommunicable diseases. Studies revealed that intestinal parasites modulate the host immune response and alter susceptibility to immunological diseases. It is suggested that one of the pathogenetic mechanisms of immune response modulation by parasites is an increase in the content of gastrointestinal bacteria with anti-inflammatory effect. Advanced technologies of microorganism identification provide a deep insight into the microbiota in different pathologies. The study of changes in the intestine and bile microbiota of the host in helminthiases provides new possibilities for prevention, diagnosis and control of such conditions as chronic inflammatory bowel diseases and allergic diseases. The purpose of this review is to analyze current experimental and clinical data on intestinal microbiota in helminth infections and possible association with development of chronic noncommunicable diseases.